1965
DOI: 10.1084/jem.122.1.59
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Bacterial Flora in the Gastrointestinal Tract of Mice

Abstract: The findings to be reported in this and the following papers reveal that mice and other mammals normally harbor an extensive bacterial flora not only in the large intestine, b u t also in the stomach and small intestine. Although this flora plays an essential role in the development and well being of its host, its exact composition is not known. In fact, several of its most important and numerous components are usually overlooked in bacteriological studies because they have exacting g r o w t h requirements, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
230
0
4

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(245 citation statements)
references
References 3 publications
11
230
0
4
Order By: Relevance
“…For example, in human infants, the initially sterile intestine is fully colonized between 1 and 2 weeks of age, and this coincides temporally with the onset of necrotizing enterocolitis, an acute inflammatory disease that is often lethal (55,56). Notably, similar colonization rates have been reported in mice (57), and the disease progression in our mice takes place over a similar time frame. Indeed, although p120 ablation in our mice occurs well before birth, differences in villus morphology were not pronounced until approximately day 10.…”
Section: Figuresupporting
confidence: 75%
“…For example, in human infants, the initially sterile intestine is fully colonized between 1 and 2 weeks of age, and this coincides temporally with the onset of necrotizing enterocolitis, an acute inflammatory disease that is often lethal (55,56). Notably, similar colonization rates have been reported in mice (57), and the disease progression in our mice takes place over a similar time frame. Indeed, although p120 ablation in our mice occurs well before birth, differences in villus morphology were not pronounced until approximately day 10.…”
Section: Figuresupporting
confidence: 75%
“…Such bacteria-yeast interactions have also been observed in patients with urinary candidosis (Marrie and Costerton,198 l). The inability of C. albicans to associate with the intestinal mucosa of untreated (control) animals in this study was probably due to the presence of the indigenous anaerobic bacteria, that are absent in neonatal or antibiotic-treated animals (Schaedler et al, 1965;Davis et al, 1973), and that inhibit the mucosal association of C. albicans by forming a dense layer of bacteria in the mucous gel, depriving the yeast cells of adhesion sites, and producing inhibitor substances (e.g., volatile fatty acids) that modify the surface properties of C. albicans or mucosal receptors (Kennedy and Volz, 1985a). The antibiotic treatments used here modified the caecal environment and reduced the total concentrations of VFA in the animals' caeca.…”
Section: Discussionmentioning
confidence: 72%
“…It has been reported that indigenous mucosaassociated bacteria reduced the association of C. albicans with the intestinal wall, and this reduced the ability of Candida to colonise the GI tract and spread systemically to visceral organs (Kennedy and Volz, 1985a and b). In infant mice that lack a complete bacterial flora, including the dense microbial populations in the mucous gel (Schaedler et al, 1965;Davis et al, 1973), C. albicans was found to associate readily with the gut wall and to pass through the mucosa to initiate systemic infection (Pope et al, 1979;Field et al, 1981). These studies also showed that Candida cells adhered to the secreting epithelium and keratinised epithelium of the stomach and the epithelial surface of the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…AI-2 activity was not detected in non-supplemented broth from wild-type species or the luxS species. Schaedler broth is a general purpose liquid medium for the growth of fastidious aerobic and anaerobic bacteria (Schaedler et al, 1965) that has been used in the testing of oral bacteria for the production of AI-2 (Frias et al, 2001). Until now, Schaedler broth has not been supplemented with boric acid and requirement for boric acid to detect AI-2 produced by streptococci in Schaedler broth has not been shown before, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%